Respuestas

  • Usuario de Brainly
2013-07-01T22:18:50+02:00
Primero resolve los parentesis y luego las llaves

a)- (6-3) - [2 - (5-7) - 3] =
   - ( 3) -
[2 - ( - 2) - 3] =
  
- ( 3) - [2  +  2 - 3] =
   - ( 3) - [ 1 ] =
   - 3 - 1 = - 4

 
b) 2 + { - [ -(7+8) + (4-3)]-2}
   
2 + { - [ - 15 +  1]- 2} =
    2 + { - [ - 14]- 2} =
    2 + { 14 - 2} =
    2 + 12 = 14

 
c) - [5 - (4-7) - (2-3)] =
      - [5 - (- 3) - (- 1)] =
     -
[5 +  3 +  1] =
     
- [ 9 ] =  -  9

d) - (7-3) - (5-2) - [(12-6) - (9-5)]
=
- ( 4 ) - (3 ) - [(12-6) - (9-5)] =
 - 4 - 3 - [ 6  - 4 ] =
 - 4 - 3 - 2  = - 9

espero que te sirva, salu2!!!!